Rancang Bangun Sistem Monitoring Air Tawar Yang Berkualitas Pada Fresh Water Generator Di Atas Kapal MT. Alpha Point - Andhika Bintang Narottama; Antonius Edy Kristiyono; Akhmad Kasan Gupron (Pusat Riset dan Inovasi Nasional, 2024)
Water is the most abundant thing on earth. However, in reality, the water on ships is not always considered consumable. This is caused by the FWG (Fresh Water Generator) auxiliary machine processing process. FWG is a ship auxiliary engine that produces fresh or salt water through a distillation process. FWG carries out distillation using a heat source from the jacket for the evaporation process to produce fresh water. The accuracy of the salt content produced through FWG is not yet known. If processed FWG products whose salt content is unknown are still consumed, it will have a negative impact on health, such as: kidney failure and the risk of developing kidney stones. Based on this problem, a tool was designed to monitor the salt content of processed FWG on board ships so that it could be used by all crew members and passengers. According to quality standards, the salt content that can be consumed by humans is below 50 ppm, with a pH between 5.0 to 7.5 and a turbidity of between 5 and 25 NTU. By designing this tool, we will be able to monitor the suitability of FWG fresh water so that it can be consumed on board. With the help of LCD, it will be able to help provide information regarding monitoring results of water quality. In testing this tool, the pH sensor, turbidity sensor and salinometer conductivity sensor will help to test the suitability of fresh water.